Critical size for reproduction and ontogenetic changes in the allocation patterns of wild and domesticated species of evening primrose (Oenothera L.) - Jaramillo, Gabriela Cecilia (2015)
Oenothera L. (evening primrose) has been suggested as a new seed-oil crop, source of gamma-linolenic acid, with uses herbal medicine industries. We compared the critical size for reproduction and the biomass allocation patterns during three phenological stages of a wild (O. mendoncinensis) and a domesticated species (O.biennis). Rosettes of O. biennis attained a critical size after two years in the field, while the wild species reproduced during the first year. Early bolting is a comprehensive strategy for indeterminate species growing in a short season environment, because it extends the flowering period but at the same time, the short vegetative period limits carbohydrates stores available for reproductive growth, and therefore, yield. Reproductive effort caused in both species a significant depletion of reserves during the flowering. Leaves and roots biomass declined by senescence after bolting in the wild species. In conclusion, yield improvement of wild species of Oenothera could be obtained by selecting plants with higher accumulation of vegetative biomass and delayed senescence that guarantees greater photosynthetic capacity after flowering.